The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1440-1789.2006.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy case of neuro‐Behçet’s disease with multifocal neutrophilic perivascular inflammation

Abstract: We report here an autopsy case of neuro-Behçet's disease. The patient was a 28-year-old man, who developed a slight fever, right uveitis, and right sensory neural hearing loss at the age of 25. These symptoms relapsed repeatedly despite treatment. Eventually he was admitted to hospital because of progressing neurological deficits such as pyramidal symptoms, somatic sensorial and autonomic disorders, and bulbar palsy. The patient's condition deteriorated and he died of heart failure. Total clinical course was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…The preferential involvement of the white matter in some series can also be explained by geographic and ethnic differences [21]. This finding, consistent with small vessels disease/vasculitis (in keeping with the neuropathological findings in NB that showed an inflammatory perivasculitis) [22,23] has been helpful in supporting parenchymal involvement in BD. However, it lacks specificity, as it may also be described in other vasculitis and also in some inflammatory demyelinating diseases.…”
Section: Discussionsupporting
confidence: 69%
“…The preferential involvement of the white matter in some series can also be explained by geographic and ethnic differences [21]. This finding, consistent with small vessels disease/vasculitis (in keeping with the neuropathological findings in NB that showed an inflammatory perivasculitis) [22,23] has been helpful in supporting parenchymal involvement in BD. However, it lacks specificity, as it may also be described in other vasculitis and also in some inflammatory demyelinating diseases.…”
Section: Discussionsupporting
confidence: 69%
“…Si bien la clásica histología del Behçet es una vasculitis de vaso pequeño, esto rara vez se demuestra a nivel de SNC, encontrándose zonas de células apoptóticas y un infiltrado inflamatorio perivascular 13 . En cuanto al estudio del compromiso neurológico en Behçet, el LCR puede ser normal y en caso de estar alterado los hallazgos más frecuentes son la pleocitosis y la hiperproteinorraquia.…”
Section: Discussionunclassified
“…In the progressive phase, authors found the inflammatory infiltration of lymphocytes and cytokines remains and cuts down. (Hirohata et al, 2008;Heo et al, 2008;Hadfi et al, 1996;Arai et al, 2006;Scardamaglia et al, 2001). …”
Section: Classificationmentioning
confidence: 99%